Recent Updates on the Anticancer Activity of Quinoxaline Hybrids (Jan. 2017-Jan. 2022) - Feng, Lian-Shun; Gao, Chuan; Liu, Fa-Wu; Wang, Xiao-Ping; Zhang, Zhi-Liu (Current Topics in Medicinal Chemistry, 2022)
Cancer being one of the leading causes of death among non-communicable diseases, has already posed a heavy burden on the world health system. Chemotherapy is one of the most effective approaches for cancer treatment, but multidrug resistance, lack of efficacy, and toxic side effects hamper efficacious cancer chemotherapy, creating an urgent need to develop novel, more effective and less toxic anticancer therapeutics. Quinoxalines, as fascinating structures, constitute an important class of heterocycles in drug discovery. Quinoxaline hybrids could exert anticancer activity through diverse mechanisms and possess profound in vitro and in vivo efficacy against various cancers, including multidrug-resistant forms. Thus, quinoxaline hybrids represent useful templates for the control and eradication of cancer. The purpose of the present review article is to provide an emphasis on the recent developments (Jan. 2017-Jan. 2022) in quinoxaline hybrids with insights into their in vitro and in vivo anticancer potential as well as structure-activity relationships (SARs) to facilitate further rational design of more effective candidates.
Keywords: Structure-activity relationships